2007
DOI: 10.1039/b708456k
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic modification of disulfonated aluminium phthalocyanine fluorescence in a macrophage cell line

Abstract: Disulfonated aluminium phthalocyanine (AlS(2)Pc) is used experimentally as a photosensitiser for both photodynamic therapy (PDT) and photochemical internalisation (PCI). In this study we have focused on modifications in intracellular photosensitiser localisation and fluorescence intensity in macrophages during and after photoirradiation. Since macrophages are highly abundant in tumour tissue and readily accumulate AlS(2)Pc both in vivo and in vitro, we investigated PDT-induced changes of AlS(2)Pc fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Because these molecules already have the amphiphilic arrangements that permit better membrane incorporation, it is likely that liposomes compete with cells for these sens compounds, leading to lower cellular incorporation and photo-induced cell death. Among the compounds obtained by functionalization at positions 13 3 and 17 3 (6, 7, 8, 9 and 10), 8 presents similar behavior to that of Hp IX (10), whereas the amines and quaternary ammonium derivatives are around four times more photocytotoxic than Hp IX. The higher photocytotoxic activity of these compounds was attributed to their amphiphilic structure, with favorable logP o/w , and to the positive charges that may favor their interactions with mitochondria.…”
Section: Cytotoxicity and Photocytotoxicitymentioning
confidence: 56%
See 2 more Smart Citations
“…Because these molecules already have the amphiphilic arrangements that permit better membrane incorporation, it is likely that liposomes compete with cells for these sens compounds, leading to lower cellular incorporation and photo-induced cell death. Among the compounds obtained by functionalization at positions 13 3 and 17 3 (6, 7, 8, 9 and 10), 8 presents similar behavior to that of Hp IX (10), whereas the amines and quaternary ammonium derivatives are around four times more photocytotoxic than Hp IX. The higher photocytotoxic activity of these compounds was attributed to their amphiphilic structure, with favorable logP o/w , and to the positive charges that may favor their interactions with mitochondria.…”
Section: Cytotoxicity and Photocytotoxicitymentioning
confidence: 56%
“…Three different routes were used to obtain seven new photosensitizers derived from Hp IX: modification at positions 3 1 and 8 1 , 13 3 and 17 3 , or of all four positions simultaneously. Analysis of the photophysical, biophysical and photocytotoxic properties showed that it is possible to correlate structural changes with compound behavior in vitro and in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition and interpretation of PpIX photobleaching measurements in vivo is a complex task and studies in the literature addressing these issues are somewhat conflicting (6)(7)(8)10,11,(20)(21)(22). The intrinsic mechanism of photobleaching has been shown to be photosensitizer specific (23)(24)(25)(26)(27). This has important consequences for the general interpretation of photobleaching as a dose metric for PDT (28).…”
Section: Monitoring the Kinetics Of Ppix Photobleachingmentioning
confidence: 99%
“…Excitation of the PS results in the production of reactive oxygen species (ROS), particularly singlet oxygen which can oxidise important subcellular substrates including membrane components such as unsaturated lipids and cholesterol. Like PDT, PCI also relies on the presence of molecular oxygen for generation of ROS, although since oxygen solubility in organelle membranes is relatively high only strongly hypoxic cells should be unaffected by PCI . However these two treatments differ in key aspects (Fig.…”
Section: Mechanism Of Pcimentioning
confidence: 99%